Effect of pressure on the phase transition behavior of ammonium nitrate - Mondal, T.K.; Shivaprakash, N.C.; Rajanna, K. (Физика и техника высоких давлений, 2004)
Ammonium nitrate (AN) is used as oxidizer in solid propellants, explosives, gas generator systems and also as a fertilizer. AN crystallizes in five polymorphic phases that appear at different temperatures. Phase transition of AN from one polymorphic phase to another is very important as an oxidizer and also as fertilizer. During its use as an oxidizer, whether pressure plays any role in phase transition is described in this paper. High Pressure−Differential Thermal Analysis (HP−DTA) system is used for this study.